Comparison of Milrinone with Sildenafil for the Treatment of Persistent Pulmonary Hypertension of the Newborn - Imtiaz Ahmad; Motia Javaid; Tanveer Ahmad; Imran Baloch; Nisar Khan Sajid; Abdul Razzaq Mughal (Aziz Fatimah Medical and Dental College, 2024)
Objective: To compare milrinone with sildenafil for the treatment of persistent pulmonary hypertension of the newborn. Methodology:  A single blinded randomized control trial was conducted in Department of Pediatrics, Aziz Fatima Hospital  Faisalabad from October 2022 to September 2023. 160 infants of persistent pulmonary hypertension were included through non probablity consecutive sampling. Group 1 infants (n = 80) received a loading dose of milrinone intravenously administered over a 60-minute period at a dose of 50 µg/kg. Group 2 infants (n = 80) received sildenafil (2mg per kg per dose three times a day). The medication was continued until extubation. The primary outcome variables were the mortality and duration of hospital stay. Results:   Ninety two(57.5%) of the one hubdred & sixty newborns in total were male. 111(69.4%) of the total, were full-term babies. In 114(71.2%) infants, the mode of delivery was C-section. Mortality was observed in 7 (8.8%) patients in milrinone group and 17 (21.2%) patients in sildenafil group with p-value = 0.027. Duration of hospital stay was less in milrinone group as compared to sildenafil group (14.22±3.75 days vs 17.72±5.7 days) with p-value = 0.0001. Conclusion: Milrinone has been proven to be a promising therapeutic choice for persistent  pulmonary hypertension in neonates, and it is effective in doing so in low resource settings.